2012
DOI: 10.1002/jmv.23378
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulation of hepatitis A virus genotype IIIA over the last decade in St Petersburg, Russia

Abstract: The current study, covering the period 2004-2009, is a part of long-term monitoring for hepatitis A virus (HAV) strains circulating in St Petersburg, Russia. The HAV RNA was isolated directly from the sera of hepatitis A patients and RT-PCR was carried out using primer pairs for VP1/2A and VP1 genomic regions. PCR products were sequenced and 324 nucleotides from VP1/2A and 332 from the VP1 region were used for phylogenetic analysis. The results show that the IA subtype was the most common circulating subtype d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…Phylogenetic analysis showed that the subtype IA isolates were 93% homologous to the sequences isolated in the European part of Russia, which formed a single phylogenetic cluster. This is consistent with reports on hepatitis A virus genomic variants circulating in the European part of Russia [ 13 , 19 ]. The identified subtype IB strains had maximum homology with isolates from Egypt and Bulgaria, which indicated probable imported cases of hepatitis A infection [ 20 ].…”
Section: Resultssupporting
confidence: 93%
“…Phylogenetic analysis showed that the subtype IA isolates were 93% homologous to the sequences isolated in the European part of Russia, which formed a single phylogenetic cluster. This is consistent with reports on hepatitis A virus genomic variants circulating in the European part of Russia [ 13 , 19 ]. The identified subtype IB strains had maximum homology with isolates from Egypt and Bulgaria, which indicated probable imported cases of hepatitis A infection [ 20 ].…”
Section: Resultssupporting
confidence: 93%
“…Several HAV outbreaks due to consumption of berries and vegetables have been reported previously (Butot et al 2007 ). Reports on contamination of vegetables from several parts of the world (Mukomolov et al 2012 ; Hernández et al 1997 ; Felix-Valenzuela et al 2012 ) indicate the gravity of the situation.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained give confidence the method can be sensibly applied to actual surveillance datasets. Examples of existing large molecular epidemiological databases include VNTR typing datasets of tuberculosis [22], spa typing datasets of MRSA [23] and short read sequencing datasets of hepatitis B, hepatitis A and norovirus [24][26]. Note that the relevant spatial information differs for these datasets; we might focus on place of residence for tuberculosis, but on hospital, ward or even bed for MRSA.…”
Section: Discussionmentioning
confidence: 99%